BNT162b2 mRNA Vaccination Against Coronavirus Disease 2019 is Associated With a Decreased Likelihood of Multisystem Inflammatory Syndrome in Children Aged 5–18 Years—United States, July 2021 – April 2022. (20th August 2022) - Zambrano, Laura D; Newhams, Margaret M; Olson, Samantha M; Halasa, Natasha B; Price, Ashley M; Orzel, Amber O; Young, Cameron C; Boom, Julie A; Sahni, Leila C; Maddux, Aline B; Bline, Katherine E; Kamidani, Satoshi; et al.
Abstract: Background: Multisystem inflammatory syndrome in children (MIS-C), linked to antecedent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is associated with considerable morbidity. Prevention of SARS-CoV-2 infection or coronavirus disease 2019 (COVID-19) by vaccination might also decrease MIS-C likelihood. Methods: In a multicenter, case-control, public health investigation of children ages 5–18 years hospitalized from 1 July 2021 to 7 April 2022, we compared the odds of being fully vaccinated (2 doses of BNT162b2 vaccine ≥28 days before hospital admission) between MIS-C case-patients and hospital-based controls who tested negative for SARS-CoV-2. These associations were examined by age group, timing of vaccination, and periods of Delta and Omicron variant predominance using multivariable logistic regression. Results: We compared 304 MIS-C case-patients (280 [92%] unvaccinated) with 502 controls (346 [69%] unvaccinated). MIS-C was associated with decreased likelihood of vaccination (adjusted OR [aOR]: .16; 95% CI: .10–.26), including among children ages 5–11 years (aOR: .22; 95% CI: .10–.52), ages 12–18 years (aOR: .10; 95% CI: .05–.19), and during the Delta (aOR: .06; 95% CI: .02–.15) and Omicron (aOR: .22; 95% CI: .11–.42) variant-predominant periods. This association persisted beyond 120 days after the second dose (aOR: .08; 95% CI: .03–.22) in 12–18-year-olds. Among all MIS-C case-patients, 187 (62%) required intensive care unit admission and 280 (92%) vaccine-eligible case-patients were unvaccinated. Conclusions: Vaccination with 2 doses of BNT162b2 is associated with reduced likelihood of MIS-C in children ages 5–18 years. Most vaccine-eligible hospitalized patients with MIS-C were unvaccinated. Abstract : We conducted a multicenter public health investigation of hospitalized vaccine-eligible US patients ages 5–18 years comparing 304 MIS-C patients with 502 SARS-CoV-2–negative controls. BNT162b2 vaccination was associated with a decreased likelihood of MIS-C across periods of Delta and Omicron predominance.